2010
DOI: 10.1002/sca.20181
|View full text |Cite
|
Sign up to set email alerts
|

Applying tribology to teeth of hoofed mammals

Abstract: Mammals inhabit all types of environments and have evolved chewing systems capable of processing a huge variety of structurally diverse food components. Surface textures of cheek teeth should thus reflect the mechanisms of wear as well as the functional traits involved. We employed surface textures parameters from ISO/DIS 25178 and scale-sensitive fractal analysis (SSFA) to quantify dental wear in herbivorous mammals at the level of an individual wear enamel facet. We evaluated cheek dentitions of two grazing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
158
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(169 citation statements)
references
References 35 publications
5
158
0
6
Order By: Relevance
“…between certain distantly related taxa), but to document differences in diet when they might not necessarily be expected based on tooth morphology alone. Differences between closely related taxa have been captured, for instance, in bovids (Scott, 2012; Ungar, Merceron, & Scott, 2007), cervids (Berlioz, Kostopoulos, Blondel, & Merceron, 2017), ungulates (Schulz, Calandra, & Kaiser, 2010), feliforms (DeSantis & Haupt, 2014; DeSantis, Tseng, et al, 2017), canids (DeSantis et al, 2015), primates (Scott et al, 2005; Ungar, Grine, & Teaford, 2008), and macropodids (DeSantis, Field, Wroe, & Dodson, 2017; Prideaux et al, 2009). Indeed, many bioarchaeological studies have demonstrated distinctive and predictable diet‐related differences in both gross dental wear and microwear within a single species, Homo sapiens (Rose & Ungar, 1998).…”
mentioning
confidence: 99%
“…between certain distantly related taxa), but to document differences in diet when they might not necessarily be expected based on tooth morphology alone. Differences between closely related taxa have been captured, for instance, in bovids (Scott, 2012; Ungar, Merceron, & Scott, 2007), cervids (Berlioz, Kostopoulos, Blondel, & Merceron, 2017), ungulates (Schulz, Calandra, & Kaiser, 2010), feliforms (DeSantis & Haupt, 2014; DeSantis, Tseng, et al, 2017), canids (DeSantis et al, 2015), primates (Scott et al, 2005; Ungar, Grine, & Teaford, 2008), and macropodids (DeSantis, Field, Wroe, & Dodson, 2017; Prideaux et al, 2009). Indeed, many bioarchaeological studies have demonstrated distinctive and predictable diet‐related differences in both gross dental wear and microwear within a single species, Homo sapiens (Rose & Ungar, 1998).…”
mentioning
confidence: 99%
“…Butler himself (1978, p. 451) stated: 'Let those who are contemplating the introduction of new names pause to consider whether in so doing they are advancing the subject or making it more difficult to understand' . We aim for a broader comparative nomenclature that helps to describe facets for dental occlusion analysis (Kullmer et al 2009(Kullmer et al , 2012Fiorenza et al 2011;Benazzi et al 2013) and the analysis of masticatory biomechanics (Schulz & Kaiser 2010;Calandra et al 2012; offer the opportunity to characterize facets in more detail. Kaiser and Brinkmann (2006) introduced a labeling system of occlusal enamel ridge patterns in bovids and equids as a strictly function-orientated system that numbers facets (adopted from Janis 1990).…”
Section: Challenges For Comparative Studiesmentioning
confidence: 99%
“…This system refers to the sequence of the antagonistic contact of facets, and in addition indicates the longitudinal position of the facet in relation to the cusp. Schulz and Kaiser (2010) applied the labeling system of Kaiser and Brinkmann (2006) to facets of upper and lower teeth that allow 3D surface texture measurements to infer oral behavior (e.g. diet reconstruction and chewing function) based on microscopic wear features.…”
Section: Challenges For Comparative Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Applied to biological materials, the method is nondestructive and yields information-rich data sets containing both topography and reflective intensity for each coordinate in the field of view. OT has as yet seen limited application in biology, revealing details of wear on grazing ungulate teeth in one of the few published applications (Schulz et al, 2010). Here, we apply OT technology to the analysis of the cellular makeup of the plant epidermis and, in so doing, demonstrate its high-throughput, wide spatiotemporal resolution and stunning dimensionality.…”
mentioning
confidence: 97%